Flushing manure systems for dairy facilities - Harner, Joseph P.; Murphy, James P. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2011)
Flushing systems that collect and transport manure are utilized in dairy operations. The sanitation attainable and reduced labor requirements can make flushing a desirable option. Designed flush systems utilize a flush device to effirelease the correct volume of water at the appropriate discharge rate and length of time. This achieves the designed flow velocity, contact Tatime, and depth of water in the gutter to obtain miniadequate cleaning.
Keywords: Dairy; Flushing; Manure; Separator; Lagoon